Pengaruh Pelapisan Nanokomposit SiO₂–TiO₂ dan PANI pada Kain Tekstil terhadap Nilai Sudut Kontak - Fadila Saputri; Ratnawulan, Ratnawulan (Journal of Science, Technology, and Innovation, 2025)
This study investigates the effect of SiO₂–TiO₂ nanocomposite coating with polyaniline (PANI) addition on the wettability properties of textile fabrics. The research was conducted through a laboratory-scale experimental approach by applying nanocomposite coatings onto textile substrates using the dip-coating method. Calcination temperatures of 600°C, 700°C, 800°C, and 900°C were employed to evaluate the influence of thermal treatment on surface characteristics. Wettability performance was assessed by measuring water contact angles before and after twenty washing cycles to determine coating durability. The results indicate that all coated fabrics exhibited hydrophilic behavior, characterized by contact angles below 90°, demonstrating enhanced surface affinity toward water. Variations in calcination temperature significantly affected the contact angle values, reflecting changes in surface structure and chemical properties of the nanocomposite layer. After repeated washing, a decrease in hydrophilic performance was observed, suggesting partial degradation or detachment of the coating layer. The presence of PANI, which contains polar functional groups, is considered to contribute to improved surface wettability. Overall, the SiO₂–TiO₂/PANI nanocomposite coating shows potential for functional textile applications requiring controlled hydrophilic properties, although further optimization is necessary to improve long-term stability.